2022
DOI: 10.1186/s13578-022-00919-y
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-c-Myc pathway rewires methionine metabolism for HCC progression through suppressing SIRT4 mediated ADP ribosylation of MAT2A

Abstract: Background Exploiting cancer metabolism during nutrient availability holds immense potential for the clinical and therapeutic benefits of hepatocellular carcinoma (HCC) patients. Dietary methionine is a metabolic dependence of cancer development, but how the signal transduction integrates methionine status to achieve the physiological demand of cancer cells remains unknown. Methods Low or high levels of dietary methionine was fed to mouse models wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…However, this mechanism may not be relevant under (pseudo)hypoxic conditions given that hypoxia downregulates TRIM32 protein levels as shown in pulmonary artery smooth muscle cells [61]. Thus, it remains to be determined (a) whether other SIRT4 interacting E3-Ubiquitin protein ligases, including RNF138 [60] or TRIM28 ( [60] and own unpublished results), are involved in proteasomal degradation of SIRT4, and (b) which of the lysine residues K78 and K299 are targeted by these E3-Ubiquitin ligases. Overall, our findings indicate that lysine K78 regulates protein half-life under basal conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism may not be relevant under (pseudo)hypoxic conditions given that hypoxia downregulates TRIM32 protein levels as shown in pulmonary artery smooth muscle cells [61]. Thus, it remains to be determined (a) whether other SIRT4 interacting E3-Ubiquitin protein ligases, including RNF138 [60] or TRIM28 ( [60] and own unpublished results), are involved in proteasomal degradation of SIRT4, and (b) which of the lysine residues K78 and K299 are targeted by these E3-Ubiquitin ligases. Overall, our findings indicate that lysine K78 regulates protein half-life under basal conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…39 A recent study found that SIRT4 can inhibit methionine metabolism via MAT2A methylation, inhibiting hepatocellular carcinoma progression. 41 As mentioned above, SIRT4 not only regulates glutamine metabolism in tumors but is also involved in regulating valine, leucine, isoleucine, and methionine metabolism.…”
Section: Sirt4 and Amino Acid Metabolismmentioning
confidence: 97%
“…In a pancreatic ductal adenocarcinoma (PDAC) study, SIRT4 deacetylated branched‐chain amino acid transaminase 2 (BCAT2) at lysine 44 (K44), and BCAT2 was stabilized by SIRT4 deacetylation, thereby promoting catabolism of branched‐chain amino acids, 40 whereas methylcrotonyl coenzyme A carboxylase complex (MCCC) was previously shown to interact with SIRT4 and was considered a putative substrate for SIRT4 39 . A recent study found that SIRT4 can inhibit methionine metabolism via MAT2A methylation, inhibiting hepatocellular carcinoma progression 41 . As mentioned above, SIRT4 not only regulates glutamine metabolism in tumors but is also involved in regulating valine, leucine, isoleucine, and methionine metabolism.…”
Section: Sirt4 and Cancer Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC1 signaling regulates a variety of metabolic pathways by activating transcription factors, including the oncogenic transcription factor MYC. mTORC1 activates MYC to promote hepatocellular carcinoma tumorigenesis by modulating methionine metabolism [54]. MYC can provide an advantage to cancer cells by promoting proliferation and angiogenesis, helping to evade the immune response [55].…”
Section: Mycmentioning
confidence: 99%